Bhutan : Staff Report for the 2014 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2014)
This 2014 Article IV Consultation highlights that the GDP growth in Bhutan has slowed from about 10 percent in FY2011 (July 1-June 30) to 5 percent in FY2013. Slower growth reflects policy efforts to contain overheating pressures in the form of restrictions on credit for construction and vehicle. Inflation has remained elevated, tracking closely that of India (Bhutan's main trading partner). Social development indicators have improved steadily, and Bhutan is on track or has achieved most of its Millennium Development Goals. Growth is projected to recover to 6 1\2 percent in FY2014, driven mainly by a pick-up in hydropower-related construction activities and domestic services.